How can organic rice be a boon to smallholders? Evidence from contract farming in India. (February 2018) - Mishra, Ashok K.; Kumar, Anjani; Joshi, Pramod K.; D'Souza, Alwin; Tripathi, Gaurav
Highlights: Contract farming (CF) in organic basmati rice (OBR) leads to lower yields and higher prices. CF improved the livelihood of OBR producers. Risk-loving OBR growers with CF experienced the highest loss in yields. Risk-averse OBR growers with CF received the highest prices. OBR growers who did not adopt CF would benefit from adopting it, regardless of their risk attitudes. Abstract: Demand for organic basmati rice (OBR), both at home and abroad, coupled with policy reforms have given rise to contract farming (CF) production in India. OBR production, however, is highly susceptible to weather and pest risks. This study investigates the impact of smallholders' perceived production risks on their adoption of CF in OBR farming. We also assess the impact of CF in OBR production on yields, prices received, and the livelihood of OBR producers. We use farm-level data from smallholder organic basmati rice farms in India and the endogenous switching regression method to account for heterogeneity. Although CF in OBR led to lower yields, it increased the prices producers received and improved the livelihood of OBR producers. The impact of CF varied with farmers' revealed risk attitudes. Risk-loving OBR growers with CF experienced the highest loss in yields, and risk-averse OBR growers with CF received the highest prices. We find that the OBR growers who did not adopt CF would benefit from adopting it, regardless of their risk attitudes, especially when it comes to prices received and livelihood.